Gene structure and expression of the MboI restriction--modification system. - Ueno, T (1993)
The genes from Moraxella bovis encoding the MboI restriction--modification system were cloned and expressed in Escherichia coli. Three open reading frames were found in the sequence containing the genes. These genes, which we named mboA, mboB, and mboC, had the same orientation in the genome. Genes mboA and mboC encoded MboI methyltransferases (named M.MboA and M.MboC) with 294 and 273 amino acid residues, respectively. The mboB gene coded for MboI restriction endonuclease (R.MboI) with 280 amino acid residues. Recombinant E.coli-MBOI, which contained the whole MboI system, overproduced R.MboI. R.MboI activity from E.coli-MBOI was 480-fold that of M.bovis. The amino acid sequences deduced from these genes were compared with those of other restriction--modification systems. The protein sequences of the MboI system had 38-49% homology with those of the DpnII system.